Investigating Electrochemical Stability and Reliability of Gold Electrode‐electrolyte Systems to Develop Bioelectronic Nose Using Insect Olfactory Receptor. Issue 4 (23rd January 2019) - Khadka, Roshan; Aydemir, Nihan; Carraher, Colm; Hamiaux, Cyril; Baek, Paul; Cheema, Jamal; Kralicek, Andrew; Travas‐Sejdic, Jadranka
Abstract: This article aims to demonstrate an electrochemically stable and reliable gold electrode‐electrolyte system to develop an insect odorant receptor ( Drosophila melanogaster Or35a) based bioelectronic nose. Cyclic voltammograms (CVs) and electrochemical impedance spectroscopy (EIS) of bare gold electrodes, after modification with the self‐assembled monolayer (SAM) of 6‐mercaptohexanoic acid (MHA) and after immobilization with Or35a integrated into the lipid bilayers of liposomes were conducted in the presence of four different redox probes. Potassium ferri/ferrocyanide [Fe(CN)6 ] 3− /[Fe (CN)6 ] 4− and hydroquinone (H2 Q) redox probes revealed variable and irreversible signals at the time scale of our measurements, with atomic force microscopy (AFM) images and x‐ray photoelectron spectroscopy (XPS) results suggesting gold surface etching due to the presence of CN − ions in case of [Fe(CN)6 ] 3− /[Fe (CN)6 ] 4− . Although the hexaammineruthenium complex showed stable electrochemical behaviour at all stages of biosensor development, changes in CV and EIS readings after each surface modifications were insignificant. PBS buffer as a non‐Faradaic medium, was found to provide reliable systems for electrochemical probing of modified gold electrodes with Or35a/liposomes in aqueous media. Using this system, we have shown that this novel biosensor can detect its known odorant E2‐hexenal selectively compared to methyl salicylate down to femtomolar concentration. Abstract :